The prevalence of multimorbidity in virally suppressed HIV-positive patients in Limpopo - Limakatso Lebina; Tumiso Malatji; Firdaus Nabeemeeah; Kegaugetswe Motsomi; Tsundzukani Siwelana; Khuthadzo Hlongwane; Neil Martinson (AOSIS, 2023)
Background: Non-communicable diseases (NCDs) are an emerging global public health problem. Objectives: To assess the prevalence of NCDs and their risk factors among adults on antiretroviral therapy (ART). Method: This was a cross-sectional study (July 2019 - January 2020) in Limpopo, South Africa. Patients were enrolled if they were ≥ 40 years, HIV-positive, and virologically suppressed on ART. Data were analysed descriptively, and a binomial regression model was used to identify risk factors for NCDs. Results: The majority of participants (65%; 319/488) were women. Most (83%; 405/488) were aged 40-59 years; 60% (285/472) were overweight or obese. Based on self-report, 22% (107/488) were currently smokers. Almost half (44%) 213/488) reported daily consumption of vegetables and 65% (319/488) exercised regularly and 39% (190/488) reported treatment for another chronic disease. The leading comorbid conditions were hypertension (32%; 158/488) and diabetes mellitus (5%; 24/488). Risk factors for hypertension included age 60 years and older (relative risk [RR]: 1.72; 95% confidence interval [CI]: 1.29-2.30) diabetes (RR: 1.42; 95% CI: 1.08-1.87), overweight (RR: 1.32; 95% CI: 1.03-1.69) and obesity (RR: 1.69; 95% CI: 1.32-2.17). Conclusion: There is a high prevalence, both of risk factors for NCDs and multimorbidity ( 1 chronic disease) in patients who are ≥ 40 years and virologically suppressed on ART.